Trust-based environmental regulation - Lange, B; Gouldson, A (Elsevier, 2010)
Within this paper, we examine the contribution that trust-based relationships can make to achieving better - and particularly more effective, efficient and equitable - environmental regulation. While levels of trust in regulators, regulatory processes and outcomes are often discussed, the influence of trust on different actors and on different measures of regulatory performance is poorly understood. Within this paper, we define trust-based environmental regulation as a specific regulatory style that involves openness and cooperation in interaction between regulated, regulators and third-party stakeholders in order to achieve environmental protection objectives. We then discuss the pros and cons of trust relationships between regulators, regulated businesses and citizens for achieving behavioural change towards greater environmental protection. To illustrate the significance of these issues, we then examine three forms of contractual regulatory style where trust relationships are critically important: responsive regulation, self-regulation and environmental agreements. Based on this analysis, we highlight the importance of trust-based relationships, and we argue that one of the greatest contributions of trust-based environmental regulation is to challenge how we think about regulation. Trust is often understood as enabling existing regulatory relationships or in the case of self-regulation as a complement to regulation. However, we argue that the real potential of trust is to open up new ways for participants in regulatory regimes to engage in collective actions, to go beyond a perception of regulation as driven by the competing interests of individual actors, and thus, to open up new channels of influence for behavioural change towards greater environmental protection. Our analysis therefore has great relevance for future research and for on-going debates on the future of regulation.